Making it personal: Breach and private ordering in a contract farming experiment - Sebastian Kunte; Meike Wollni; Claudia Keser (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
Contracts may be subject to strategic default, particularly if public enforcement institutions are weak. In a lab experiment, we study behavior in a contract farming game without third-party enforcement but with an external spot market as outside option. Two players, farmer and company, may conclude a contract but also breach it by side-selling or arbitrary payment reductions. We examine if and how relational contracts and personal communication can support private-order enforcement. Moreover, we investigate whether company players offer price premiums to extend the contract's self-enforcing range. We find mixed evidence for our private ordering hypothesis. Although contract breach can be reduced by relational contracts, direct bargaining communication does not additionally improve the outcome. Price premiums are offered if other enforcement mechanisms are absent, but turn out to be only an 'allurement'. Most subjects are not willing to sacrifice short-term gains in favor of a well-functioning relationship that (as we show) would be beneficial for both contract parties in the long run.
Keywords: D02; L14; Q13; 330; contract farming; private ordering; enforcement; contract breach; economic experiments; relational contracts; communication; price premiums